Menilik Komik Shingeki no Kyojin melalui Kacamata Masyarakat Simulasi Baudrillard - Ardian Indro Yuwono; Rizky Maulana Anindita (Jurnal ILMU KOMUNIKASI, 2024)
Hajime Isayama’s Shingeki no Kyojin tells the disruption on Paradis Island’s stability as Titans ambush. This article found the Paradis Island is the perfect representation of Jean Baudrillard’s simulacra society which is trapped in a chaos of reality and simulations in hyperreality. Through the Barthes’s semiotic model, this article finds that Paradis Island’s a perfect hyperreal site that traps its inhabitants in simulacra and blurs anything beyond the wall. Repression and propaganda complicate people’s understanding on politics. In reflection to current state, media are trapping society inside walls of their preferences to blur the reality behind or beyond the wall.